Packaging 4.0: The threshold of an intelligent approach. Issue 3 (12th March 2022) - Sadeghi, Kambiz; Kim, Jongkyoung; Seo, Jongchul
Abstract: The fourth industrial revolution (I4.0) intends to digitalize the product life cycle using smart technologies interconnected with web‐based platforms. I4.0 elements can be employed to enable packaging 4.0 with improved productivity and efficiency. However, the applicability of I4.0 in packaging science has not been fully investigated due to the understanding gap regarding the I4.0 elements in packaging science. In addition, the evolution of market and customers' demands results in complexity, which requires a business model with a high level of precision. As packaging stays with goods from manufacturing to the consumer stage, the digitalization of the product life cycle using packaging can be realized. Herein, the implications of I4.0 on packaging science are discussed to identify the potential benefits of packaging 4.0 in various sectors, for example, manufacturing, materials, supply chain, retail, and postconsumer. In this study, packaging 4.0 is defined based on a framework comprised of packaging manufacturing, packaging and products, packaging and consumer, and packaging and sustainability (ecologically, economically, and socially). In addition, a decentralized model is introduced to realize a self‐controlling concept using decentralized decision‐making centers. In this context, packaging 4.0 can be enabled using the combination of horizontal integration of enterprises, vertical integration of enterprises, and end‐to‐end engineering. Smart devices, for example, sensors, indicators, actuators, and wearable smart devices, interconnected to the internet of things and the cloud is an efficient way to realize a decentralized paradigm. The implementation of an intelligent platform in the packaging 4.0 context enables decentralized data collection in the supply chain, in‐store, and postpurchasing stages, which in turn realizes consistent life‐cycle monitoring.